«23 Zhoktau» of Alash – «Zhoktau» Symbol of Freedom - Kamzabekuly, Д. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
This article considers literature as one of the types of art that has both an aesthetic and ideological goal. While artistry is based on feelings and tastes, the idea is based on the demands and interests of the nation and country. Since ancient times, the Kazakh people understood the importance of the world and responsibly treated earthly and eternal life. It was believed that earthly life is a preparation for eternal life, and a person must account to the spirit of the deceased (aruahs). Following one to his grave was performed as a special ritual. The poetic image of this rite is Zhoktau (crying for the dead). During the years of Bolshevism, the cultural intelligentsia «Alash» released «23 Zhoktau» as a separate compilation. In this book, life stories of great personalities who fought for the development and freedom of the Kazakh people are presented in a poetic form. At first glance, the form of the narrative could seem like a “national heritage”, but the actual content was “crying for freedom”. «23 Zhoktau» was prepared by prominent figures like Ahmet Baitursyn-uly and Alikhan Bokeikhan. We can safely say that this compilation that includes hopes and aspirations, sadness and suffering, pride and wisdom of four centuries, is a symbol of Zhoktau for freedom